Supramolecular structures based on regioisomers of cinnamyl-α-cyclodextrins - new media for capillary separation techniques - Benkovics, Gabor; Hodek, Ondrej; Havlikova, Martina; Bosakova, Zuzana; Coufal, Pavel; Malanga, Milo; Fenyvesi, Eva; Darcsi, Andras; Beni, Szabolcs; Jindrich, Jindrich (Beilstein journal of organic chemistry, 2016)
This work focuses on the preparation and application of supramolecular structures based on mono-cinnamyl-α-cyclodextrins (Cin-α-CD). Pure regioisomers of Cin-α-CD having the cinnamyl moiety at the 2-O- or at the 3-O-position, respectively, were prepared, characterized and applied in capillary electrophoresis as additives to the background electrolyte. These new monomer units with a potential to self-organize into supramolecular structures were synthesized via a straightforward one-step synthetic procedure and purified using preparative reversed-phase chromatography allowing a large scale separation of the regioisomers. The ability of the monomers to self-assemble was proved by various methods including NMR spectroscopy and dynamic light scattering (DLS). The light scattering experiments showed that the monomer units have distinguishable ability to form supramolecular structures in different solvents and the size distribution of the aggregates in water can be easily modulated using different external stimuli, such as temperature or competitive guest molecules. The obtained results indicated that the two regioisomers of Cin-α-CD formed different supramolecular assemblies highlighting the fact that the position of the cinnamyl group plays an important role in the intermolecular complex formation.
Keywords: regioisomers; cyclodextrin derivatives; capillary electrophoresis; mono-cinnamyl; supramolecular structures